Moderasi Kecerdasan Adversitas dan Resiliensi Terhadap Pengaruh Motivasi Karier pada Minat Memperoleh Sertifikasi Chartered Accountant - Dewi, Anak Agung Sagung Mas Swandari; Dewi, Luh Gede Krisna (E-Jurnal Akuntansi, 2023)
This study aims to examine the effect of career motivation and the moderating effect of adversity intelligence and resilience on the interest in obtaining a Chartered Accountant (CA) certification. The study used a sample of 98 accounting students. The method of determining the sample used is purposive sampling. The study uses primary data derived from the answers to the questionnaires that have been distributed to the respondents. The analysis technique in this research uses Moderated Regression Analysis (MRA). The results of the study show that career motivation and resilience have a positive and moderating effect on the interest of accounting students to obtain Chartered Accountant (CA) certification. Keywords: Career Motivation; Adversity Intelligence; Resilience; Interest in  Obtaining CA Certification